Ecology as a design orientation in the form of contemporary industrial products (Eurasian Journal of Research, Development and Innovation, 2024)
The current research discussed the topic of (ecology as a design trend in the form of the contemporary industrial product), where the researcher addressed the research problem, which focused on the following question: Do ecological systems represent a design trend that affects the form of the contemporary industrial product? The importance of this research has emerged as it sheds light on ecology and its impact on the design of the contemporary industrial product, which enables specialists to benefit from its results in enhancing their design ideas. The aim of this study is to identify ecological systems and their design orientations that can be subject to the form of the contemporary industrial product. As for the second chapter, it contained the theoretical framework of the research, which included three topics. The first topic discussed the ecological system and its mechanisms in design, and the second topic included the theoretical ecological orientations in contemporary industrial design, while the third topic included the design form of the industrial product in light of ecological standards. Then the research concluded with its literary, intellectual and environmental proposals. Then the research adopted the descriptive approach in analyzing the research sample, the furniture of the French company Wild Design, and the devices of the Chinese company Powerstar from 2014 to 2016, which are available in global markets. It included analyzing and describing the samples, and the results and conclusions of the research were reached